Financial Turmoil and Choice of Exchange Rate Regime - Ricardo Hausmann; Michael Gavin; Carmen Pagés-Serra; Ernesto H. Stein (Inter-American Development Bank, Office of the Chief Economist, 1999)
Financial turmoil is becoming a fact of life in Latin America. The 1990s have been characterized by enormous volatility in the magnitude and cost of capital flows. The correlation of capital swings across disparate countries suggests that the quality of emerging market policies in addition to global factors have been the main actors in this drama. Therefore, the blame for financial turmoil has moved away from inappropriate domestic policies. Instead, the paradigm has shifted to one of determining which policies domestic or international are most effective in taming the destabilizing effects of inherently volatile capital flows.
Keywords: 330; Volatilität; Finanzmarkt; Wechselkurssystem; Geldpolitik; Zins; Kapitaleinkommen; Lateinamerika